1989
DOI: 10.2135/cropsci1989.0011183x002900040050x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Restriction Fragment Length Polymorphisms among Maize Inbreds with Agronomic Performance of Their Crosses

Abstract: Restriction fragment length polymorphisms (RFLPs) have been suggested as molecular markers to facilitate improvement of agronomic traits in maize (Zea mays L.). The objective of this study was to evaluate the utility of RFLP data in elucidating heterotic patterns among maize lines. Eight maize inbred lines and their 28 singlecross hybrids werevaluated for grain yield at two Iowa locations in each of 2 yr in a randomizedcomplete block design. The diallel mating design permitted estimation of general and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
89
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 0 publications
14
89
0
2
Order By: Relevance
“…For example, the association of genetic distance with heterosis in elite inbred lines of corn may be very strong (Lee et al, 1989;Smith et al, 1990) or weak (Godshalk et al, 1990;Dudley et al, 1991), because the correlation between marker distance and F 1 performance depends on the origin of lines studied (Melchinger et al, 1990;Boppenmaier et al, 1993). Genetic background plays an important role in heterosis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the association of genetic distance with heterosis in elite inbred lines of corn may be very strong (Lee et al, 1989;Smith et al, 1990) or weak (Godshalk et al, 1990;Dudley et al, 1991), because the correlation between marker distance and F 1 performance depends on the origin of lines studied (Melchinger et al, 1990;Boppenmaier et al, 1993). Genetic background plays an important role in heterosis.…”
Section: Introductionmentioning
confidence: 99%
“…The RFLPs are attractive markers because they are generally numerous, co-dominant, phenotypically neutral and insensitive to plant growth environment. The RFLP techniques have been applied to a wide range of theoretical and applied genetic studies such as mapping genes of economic value (Diers et al, 1992), identifying useful germplasm (Zehr et al, 1992), resolving phylogenetic relation-ships among taxa (Song et al, 1990) and diallel analysis of quantitative traits (Lee et al, 1989;Smith et al, 1990). The RFLPs provide an opportunity to more precisely measure genetic differences among individuals compared to morphological or biochemical markers because these are generally abundant in populations of interest, have no apparent effect on plant fitness per se and are not affected by the environment (Soller and Beckmann, 1983).…”
Section: Intmentioning
confidence: 99%
“…Molecular methods allow the varietal characterization with high discrimination power. Several studies have shown the quality of information on the molecular identification of germplasm (Lee et al,1989;Smith & Smith, 1991). Marker-assisted selection: The possibility of identifying genes of interest, to be strongly linked to molecular markers allows the selection can be made indirectly.…”
Section: Characteristicsmentioning
confidence: 99%